2000
DOI: 10.1111/j.1532-5415.2000.tb03147.x
|View full text |Cite
|
Sign up to set email alerts
|

Living and Dying with Chronic Obstructive Pulmonary Disease

Abstract: OBJECTIVE: To characterize chronic obstructive pulmonary disease (COPD) over patients' last 6 months of life. STUDY DESIGN: A retrospective analysis of a prospective cohort from the Study to Understand Prognoses and Preferences for Outcomes and Risks of Treatments (SUPPORT). SETTING:Hospitalization for exacerbation of COPD at five US teaching hospitals. PARTICIPANTS: COPD patients who died within 1 year (n = 416) among 1016 enrolled. METHODS: Interview and medical record data were organized into time windows b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
1
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(144 citation statements)
references
References 37 publications
4
133
1
6
Order By: Relevance
“…It may well be that CF, with its relapsing and remitting pattern of disease advancement, the dramatic increases in life expectancy over the past few decades, and the increasingly available option of lung transplantation, is simply not a suitable fit for the existing methods of ACP, such as health care proxies and living wills. The disease trajectory of CF in some ways mimics that of congestive heart failure or adult chronic obstructive pulmonary disease, 30 with the important difference of a lifelong experience of illness beginning in childhood. A qualitative study in the UK found that patients and clinicians identified the need for integration of ACP early in the course of disease progression, allowing for co-existence of palliative and therapeutic care over time.…”
Section: Sawicki Et Al 1138mentioning
confidence: 99%
“…It may well be that CF, with its relapsing and remitting pattern of disease advancement, the dramatic increases in life expectancy over the past few decades, and the increasingly available option of lung transplantation, is simply not a suitable fit for the existing methods of ACP, such as health care proxies and living wills. The disease trajectory of CF in some ways mimics that of congestive heart failure or adult chronic obstructive pulmonary disease, 30 with the important difference of a lifelong experience of illness beginning in childhood. A qualitative study in the UK found that patients and clinicians identified the need for integration of ACP early in the course of disease progression, allowing for co-existence of palliative and therapeutic care over time.…”
Section: Sawicki Et Al 1138mentioning
confidence: 99%
“…They may describe disabling shortness of breath, depression, cough, fatigue, pain, confusion, anorexia, or thirst [5][6][7][8]. This morbidity is reflected in severe impairment of quality of life and activities of daily living [5,6,9]. Social isolation is common [5].…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation is common [5]. Exacerbations may result in frequent hospital admissions and high use of primary care services [5,9] C o p y r ig h t G e n e r a l P r a c t ic e A ir w a y s G r o u p R e p r o d u c t io n p r o h ib it e d is high, but less than half have access to appropriate social and nursing support [5][6][7]9]. Unmet spiritual distress increases anxiety, panic attacks and the unscheduled use of medical services [10].…”
Section: Introductionmentioning
confidence: 99%
“…Pain, dyspnea, fatigue, and anxiety are common symptoms experienced at the end-of-life with most patients who die in the hospital suffering moderate to severe symptoms (Cantor et al 2003, Desbiens et al 1996, Lynn et al 2000. The SUPPORT study found that 50% of patients who were conscious prior to death in the hospital experienced moderate to severe pain at least half of the time.…”
Section: The Medical Model Of Dyingmentioning
confidence: 93%